Efforts to Increase Employee Performance Through Transformational Leadership and Human Resource Development (Study of Sibolga City Government) - Fauziah Nur Simamora; Wilson Bangun; Sofyan Matondang (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
This research aims to analyze the influence of transformational leadership style and human resource development on the performance of State Civil Service employees in the District Government in Sibolga City. This research uses a quantitative approach, with a quantitative method in the form of a survey. The researcher determined that the sample in the research was all Civil Servants in 4 sub-districts, including the village head in each sub-district, with a total of 160 people. The researchers took the entire population to be used as a sample of 160 people. Research results show that transformational leadership style on proven performance influential significant. The development source Power humans also matter positively and significantly to performance. However, a variable that influences performance is style leadership transformational. Coefficient results in determination in study This shows that mark R The adjusted square on performance is 0.7 64 (76.4%). This means that style leadership transformational and developmental source Power man contribute 76.4% to performance. Whereas the other side is 23.6% influenced by other variables not included in the study.